Chemical Composition of High-T\(_C Ge_1 - xMn_x\) Nanocolumns Grown on \(Ge(001)\) Substrates - Giang, Le Thi; An, Nguyen Manh (Communications in Physics, 2014)
By mean of molecular beam epitaxy (MBE) equipped with a reflexion high-energy electron diffraction (RHEED) technique, we have chosen an intermediate and appropriate substrate temperature of 130\(\)C to reproducibly synthetize high-T\(_C\) Ge\(_1 - x\)Mn\(_x\) nanocolumns phase. Laser Pulse Atom Probe Tomography (LP-APT) technique have been used to determine at atomic scale the chemical composition inside nanocolumns and also in the surrounding diluted matrix. The Mn concentration inside nanocolumns is found to be highly inhomogeneous, it is about 20\(%\) at the bottom and can increase up to \(40%\) in the top near the surface region. The Mn concentration in the matrix is about 0.25\(%\) at the surface and can reach a highest value of 1% in regions close to the interface.